Development of an information and communication technology (ICT) tool for monitoring of antimicrobial use, animal disease and treatment outcome in low-income countries - Sternberg-Lewerin, S.; Onono, J.O.; Boqvist, S.; Mugisha, L.; Kihara, W.; Lindfors, L.; Strandell, K.; Mutua, Florence K. (MDPI, 2025)
Background/Objectives: Surveillance of antimicrobial resistance (AMR) and antimicrobial use (AMU) is needed to understand risks and implement policies. Collecting AMU data in the context of disease prevalence and therapeutic outcomes has been suggested for improving AMU. We describe the process of developing an information and communication technology (ICT) system to monitor AMU, diseases and treatment outcomes in poultry in East Africa.